PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES DENGAN MODEL PJBL PADA MATA PELAJARAN MATEMATIKA DI KELAS IV SEKOLAH DASAR - Resti Laila Hasanah; Firman; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to develop Google Sites-based learning media with the Project-Based Learning (PjBL) model to improve mathematics learning in grade IV of Elementary School. The background of this study is the low motivation and learning outcomes of students due to monotonous learning methods. Google Sites media is designed to be interactive, interesting, and support project-based learning that is relevant to real life. The study used the 4D development method (Define, Design, Development, Dissemination). Data were obtained through expert validation, student trials, and effectiveness analysis using pretest and posttest. The results showed that this learning media is valid, practical, and effective. Expert validation showed a high level of suitability, while trials showed an increase in student engagement in learning. The increase in student learning outcomes was confirmed through a comparison of pretest and posttest scores. In conclusion, Google Sites-based media with the PjBL model effectively improves the quality of mathematics learning and motivates students to learn more actively.